The Influence of Third-Party Funds and Other Operating Income on Profits of Islamic banking: Financing as an Intervening Variable - Zaini, Faizi; Vitaloka, Deffia Dea; Bin Shuib, Mohd Sollehudin (IKONOMIKA, 2023)
This study aims to determine the effect of third-party funds and other operating income on profits at Bank Mega Syariah with financing as an intervening variable. This research is a quantitative model using secondary data with a purposive sampling technique. The sample used is the annual report of Bank Mega Syariah for the 2012-2021 period. Data were analyzed and processed using Microsoft Excel and SPSS 25. The results found that third-party funds had a significant effect on financing. Meanwhile, other operating income has no significant effect on financing. Furthermore, third-party funds have a significant effect on net income. Other operating income and financing have no significant effect on net income. Then, financing cannot mediate the effect of third-party funds and other operating income on the net income.